Electrostatic dust cloth: a passive screening method to assess occupational exposure to organic dust in bakeries - Viegas, Carla (2018)
Organic dust is widespread in the environment including occupational settings, such as bakeries. Recently, a new collection device - the electrostatic dust cloth (EDC) - has been described for the assessment of occupational exposures. The aim of this study was to investigate the suitability of EDC for identifying the distribution patterns and exposure concentrations of particulate matter and microbial contaminants such as fungi and bacteria in bakeries. Twelve bakeries were selected, and dust was allowed to settle for 13 to 16 days on EDCs (a total of 33 samples). Particle counts and size distribution (0.3 µm, 0.5 µm, 1 µm, 2.5 µm, 5 µm and 10 µm) were measured with direct-reading equipment. Higher EDC mass was significantly correlated (p values < 0.05) with a higher fungal load on dichloran glycerol (DG18) and with particle size distribution in the 0.3 µm, 0.5 µm, 1.0 µm and 10.0 µm range. Fungal levels on malt extract agar (MEA) ranged from 0 to 2886 CFU/m2 EDC in the warehouse setting, 0 to 500 CFU/m2 EDC in the production setting, and 0 to 3135 CFU/m2 EDC in the store. Penicillium sp. (42.56%) was the most frequent fungi. Total bacterial load ranged from 0 to 18,859 CFU/m2 EDC in the warehouse, 0 to 71,656 CFU/m2 EDC in production, and 0 to 21,746 CFU/m2 EDC in the store. EDC assessment provided a longer-term integrated sample of organic dust, useful for identifying critical worksites in which particulate matter and bio-burden exposures are elevated. These findings suggest that EDC can be applied as a screening method for particulate matter-exposure assessment and as a complementary method to quantify exposures in occupational environments.